A torque ripple minimization method for brushless DC motor in high speed applications using buck boost topology - Celikel, Resat; Aydogmus, Omur (Academic Publication Council, 2019)
The torque ripple occurs due to commutation time of phase currents in the brushless direct current (BLDC) motors. In this paper, an effective method is developed to reduce torque ripple with wide speed control range for the high speed BLDC motor applications. A boost-buck converter topology has been used in this work. The boost-buck converter is placed between DC power supply and DC-link of the inverter. The DC-link voltage is adjusted depending on motor speed. Pulse Width Modulation (PWM) is used in order to control the phase currents of high speed BLDC motor. The PWM duty cycle is adjusted to reduce the ripple of the phase currents at the commutation time. The current control of the high speed BLDC motor is analyzed for three different methods. Firstly, the conventional method with constant DC-link voltage has been performed. Secondly, a variable DC-link voltage by using a boost-buck DC-DC converter has been performed. Thirdly, both variable DC-link voltage via boost-buck converter and current control method by using PWM have been performed. The waveforms of current and torque are given for different speed conditions in the steady state and during commutation. The conventional current controls and proposed current control strategies are presented by comparing performance.
Keywords: brushless DC motors; pwm; boost-buck converter; torque ripple; current commutation